“Eu sou a bucala”: a afroteca Sankofa como instrumento de combate ao racismo, ao preconceito e a discriminação na educação infantil e no Cemei Antônia Corrêa e Sousa - Santarém-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
This Capstone Project (TCC in Portuguese) aims to analyze the importance of Anti-racism Early Childhood Education with children, based on the observation and work developed at the Sankofa Afroteca, at CEMEI Antônia Corrêa e Sousa. In the first chapter, I will discuss childhood, early childhood education, and racial relations from the perspective of critics who research these topics, as well as the main legislations that address these very important and current issues. In the second chapter, I will provide a contextualization of the Kiriku Project, the CEMEI, the neighborhood, and the Sankofa Afroteca, the main result of the project in the unit. In the third chapter, I present my experience of participant observation in the Afroteca and highlight the importance of the Afroteca at CEMEI, the partnerships, the engagement with families, the practices of the teachers, the dialogues with the management and pedagogical staff, the ongoing training, the projects developed for the school's community and families, the welcoming of the children, and especially the listening to the children. I also emphasize the challenges in addressing the theme of Anti-racism education and ethnic-racial relations with the teachers and staff of CEMEI. The Sankofa Afroteca is an Anti-racism educational technology, and when used, it becomes a powerful and effective curricular and pedagogical tool in deconstructing all forms of racism, prejudice, and discrimination that may occur among children.
Keywords: Educação Antirracista Infantil; Crianças; Afroteca Sankofa; CNPQ:: CIÊNCIAS HUMANAS